918 Nasal Packing Duration in The Management of Epistaxis: A Cohort Study. (12th October 2021) - Collins, R; Addison, A; Paul, C; Clark, A; Philpott, C
Abstract: Aim: Nasal packing is one of the mainstays of inpatient treatment for epistaxis. However, no current guidelines exist on optimal duration of nasal packing. This paper seeks to determine the optimal duration of nasal packing in terms of re-bleeding. Method: A retrospective cohort study was conducted on patients admitted over a two-year period. Data collected included re-bleeding events following pack removal, age, gender, site of epistaxis, hypertension, trauma and anticoagulation medication. Results: The rate of re-bleeding increased with length of pack duration; over 12 hours was associated with greater re-bleeding rates (p = <0.001) and continued to be statistically significant when controlling for co-founders (p = 0.01). Those packed over 24 hours were over five times more likely to re-bleed than those packed less than 12 hours (p = 0.01. OR 5.34). Conclusions: A packing duration of less than 12 hours is associated with lower rates of re-bleeding. Admitting teams should therefore aim to ensure that patient pathways involve early pack removal.